Conflict and violence in South Asia : Bangladesh, India, Pakistan, and Sri Lanka - De silva, K.M.; De Silva, K. M.; International Centre for Ethnic Studies; Nederlands Instituut voor Internationale Betrekkingen "Clingendael". (Kandy : International Centre for Ethnic Studies in association with Netherlands Institute of International Relations, Clingendael, The Hague, 2000)
Selection of papers, originally presented at two conferences held on 15-17 July 1996 and 3-5 May 1997, separately at Kandy and at The Hague.
Keywords: South Asia -- Politics and government -- Congresses